MENINGKATKAN KEAKTIFAN BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN MEDIA MAGIC BOX (Studi Kasus Kelas IV SD Negeri 171/II Pedukuh Kabupaten Bungo) - Depi Novita Sari (Jurnal Tunas Pendidikan, 2022)
This research is a Classroom Action Research that aims to increase student activity and learning outcomes on FPB and KPK materials through the application of Problem Based Learning learning models with Magic Box media. This research was conducted at SD Negeri 171/II Pedukuh, with the subjects being fourth grade students in the odd semester of the 2021/2022 academic year. The data in the study were obtained based on the results of questionnaires, interviews, learning observations and learning outcomes tests. From the results of the student activity observation sheet, it was found that the percentage of student participation increased from the first cycle of 69.98% to 79.37% in the second cycle and has met the student participation indicator, namely = 75%. Based on the average value of learning outcomes obtained by students in the first cycle of 68.09, it increased to 74.81 in the second cycle and the percentage of classical completeness from 12.12% increased to 87.88% and this met the indicators of success, namely classical mastery reaching 85% with KKM 70. So it can be concluded that learning mathematics by using the Problem Based Learning learning model with Magic Box media can increase student activity and learning outcomes on FPB and KPK materials.